2014
DOI: 10.33844/mbr.2014.60211
|View full text |Cite
|
Sign up to set email alerts
|

Purchase intention of products with Islamic labels under time pressure

Abstract: The aim of this research is an investigation into the effect of using an Islamic symbol in food packaging through considering the effects of time pressure, and Involvement on Muslim consumers' purchase intention. The data gathered through questionnaire were processed using partial least-squares (PLS) method. Results represented positive and significant impact of Islamic symbol in food packaging on Muslim consumers' purchase intention. Also, the effects of time pressure as a moderating variable of relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
1
12
1
1
Order By: Relevance
“…The results obtained from the study were to demonstrate the influence of semiotic advertising efficacy on purchase intent reflect a Tvalue of 5.66 (p<0.01) and hence, the path as defined in the hypothesis seems to be acceptable. The results thus comply and align with the findings and discussions by Freire (2014), Azevedo (2016), and Akbari et al (2014) that purchase intentions of consumers go higher when the semiotic advertising adopted by a brand is effective and it can hence be suggested that brands need to focus upon and adopt such an approach of advertising and promotions for higher sales. This also implies that semiotic advertising has a strong impact in stimulating customers' purchase intent.…”
Section: Resultssupporting
confidence: 88%
“…The results obtained from the study were to demonstrate the influence of semiotic advertising efficacy on purchase intent reflect a Tvalue of 5.66 (p<0.01) and hence, the path as defined in the hypothesis seems to be acceptable. The results thus comply and align with the findings and discussions by Freire (2014), Azevedo (2016), and Akbari et al (2014) that purchase intentions of consumers go higher when the semiotic advertising adopted by a brand is effective and it can hence be suggested that brands need to focus upon and adopt such an approach of advertising and promotions for higher sales. This also implies that semiotic advertising has a strong impact in stimulating customers' purchase intent.…”
Section: Resultssupporting
confidence: 88%
“…Besides that, through the research of Farooq et al, (2015) it was also found that the higher the quality of the graphic for packaging, the likelihood of consumers feeling assured about the quality of the product. According to Akbari, Gholizadeh and Zomorrodi (2014), the picture on packaging is a way to attracting consumers buying intentions.…”
Section: Packaging Graphicmentioning
confidence: 99%
“…(3) In CCVBCs, the value of cultural and creative products is time sensitive. People react differently under time pressure, and therefore they will have different reactions in brand communities as well (Akbari et al. , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…(3) In CCVBCs, the value of cultural and creative products is time sensitive. People react differently under time pressure, and therefore they will have different reactions in brand communities as well (Akbari et al, 2014). Therefore, whether the potential time pressure will prompt community users to show different degrees of value co-creation behavior is worth further research and exploration.…”
Section: Research Limitations and Prospectsmentioning
confidence: 99%